Novel interaction between Alzheimer’s disease-related protein presenilin 1 and glutamate transporter 1 - Zoltowska, Katarzyna Marta (Sci Rep, 2018)
Neuronal hyperactivity is one of the earliest events observed in Alzheimer’s disease (AD). Moreover, alterations in the expression of glutamate transporters have been reported to exacerbate amyloid pathology and cognitive deficits in transgenic AD mouse models. However, the molecular links between these pathophysiological changes remain largely unknown. Here, we report novel interaction between presenilin 1 (PS1), the catalytic component of the amyloid precursor protein-processing enzyme, γ-secretase, and a major glutamate transporter-1 (GLT-1). Our data demonstrate that the interaction occurs between PS1 and GLT-1 expressed at their endogenous levels in vivo and in vitro, takes place in both neurons and astrocytes, and is independent of the PS1 autoproteolysis and γ-secretase activity. This intriguing discovery may shed light on the molecular crosstalk between the proteins linked to the maintenance of glutamate homeostasis and Aβ pathology.